Android E-Module Improves Reading Skills in English Language Learning: E-Modul Android Meningkatkan Keterampilan Membaca dalam Pembelajaran Bahasa Inggris - Zulfalilah, Fariza; Darmawan, Deni; Rahayu, Ayu Puji (Indonesian Journal of Innovation Studies, 2025)
General Background: In the digital era, enhancing English language competencies, especially reading skills, is essential to support students’ global communication capabilities. Specific Background: Despite its significance, reading remains a major challenge among Indonesian vocational high school students, partly due to the lack of engaging learning media. Knowledge Gap: Existing e-modules tend to rely on desktop platforms and fail to leverage the accessibility and interactivity of smartphones for independent learning. Aims: This study aimed to develop and evaluate an Android-based e-module using the ADDIE model to improve students' reading skills in English. Results: The product underwent validation by content and media experts with excellent results and was tested on 35 students in a private vocational school in Garut. Post-intervention analysis using regression techniques confirmed a positive correlation between e-module use and improved reading skills, with significant increases in post-test scores. Novelty: Unlike previous modules, this e-module integrates interactive multimedia and is accessible via mobile apps, allowing self-paced learning anytime and anywhere. Implications: The study demonstrates that Android-based e-modules are effective in enhancing reading comprehension and can serve as a scalable model for similar innovations in other subjects and language skills.Highlight : Developed an Android-based e-module using the ADDIE model to improve students' English reading skills. Validated as highly feasible by both material and media experts with >90% effectiveness. Reading skills of vocational students showed measurable improvement through linear regression analysis. Keywords : Android, E-module, Reading Skill, English Learning, ADDIE Model